Odontomas in pediatric dentistry: Report of two cases - Delbem, Alberto Carlos Botazzo [UNESP]; Cunha, Robson Frederico [UNESP]; Bianco, Karina Gerhardt [UNESP]; Afonso, Rebeca Lima [UNESP]; Gonçalves, Tais Carneiro (My University, 2005)
Odontomas are developmental disturbances which manifest in the form of denticles or amorphous informes masses comprising all dental tissues, especially enamel and dentin, with variable amounts of pulp and cement. We describe here two clinical cases of odontomas in children, focusing on diagnostic means and the importance of early treatment of these lesions. The standard treatment for the two present cases was surgical removal.
Keywords: case report; deciduous tooth; human; male; maxilla tumor; odontogenic tumor; pathology; preschool child; tooth disease; Child, Preschool; Humans; Male; Maxillary Neoplasms; Odontoma; Tooth, Deciduous; Tooth, Impacted